Barriers to and enablers of implementing antimicrobial stewardship programs in veterinary practices. (23rd March 2018) - Hardefeldt, Laura Y.; Gilkerson, J. R.; Billman‐Jacobe, H.; Stevenson, M. A.; Thursky, K.; Bailey, K. E.; Browning, G. F.
Abstract : Background: Antimicrobial stewardship (AMS) programs are yet to be widely implemented in veterinary practice and medical programs are unlikely to be directly applicable to veterinary settings. Objective: To gain an in‐depth understanding of the factors that influence effective AMS in veterinary practices in Australia. Methods: A concurrent explanatory mixed methods design was used. The quantitative phase of the study consisted of an online questionnaire to assess veterinarians' attitudes to antimicrobial resistance (AMR) and antimicrobial use in animals, and the extent to which AMS currently is implemented (knowingly or unknowingly). The qualitative phase used semi‐structured interviews to gain an understanding of the barriers to and enablers of AMS in veterinary practices. Data were collected and entered into NVivo v.11, openly coded and analyzed according to mixed methods data analysis principles. Results: Companion animal, equine, and bovine veterinarians participated in the study. Veterinary practices rarely had antimicrobial prescribing policies. The key barriers were a lack of AMS governance structures, client expectations and competition between practices, cost of microbiological testing, and lack of access to education, training and AMS resources. The enablers were concern for the role of veterinary antimicrobial use in development of AMR in humans, a sense of pride in the service provided, and preparedness to change prescribing practices. Conclusion and Clinical Importance: Our study can guide development and establishment of AMS programs in veterinary practices by defining the major issues that influence the prescribing behavior of veterinarians.